2019
DOI: 10.1021/acs.chemmater.9b02149
|View full text |Cite
|
Sign up to set email alerts
|

Surface Science and Colloidal Stability of Double-Perovskite Cs2AgBiBr6 Nanocrystals and Their Superlattices

Abstract: Capping ligand bonding and the thermal and colloidal stability of Cs 2 AgBiBr 6 nanocrystals were studied. Oleylamine and oleic acid bonding to Cs 2 AgBiBr 6 nanocrystals was studied with 1 H nuclear magnetic resonance and nuclear Overhauser effect spectroscopy. Both molecules are present in the ionic metathesis synthesis reaction, but only oleylamine remains bound to the nanocrystals after purification. Oleic acid is not a capping ligand; however, the synthesis requires it, and its concentration determines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
75
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 43 publications
4
75
3
Order By: Relevance
“…These findings, which are substantially different from what observed in Cs 2 AgBiBr 6 NCs (where akylammonium ions only have been detected), 14 point to a complex ligand shell in which ligands are homogeneously intermixed on the surface of perovskite NCs.…”
contrasting
confidence: 91%
See 2 more Smart Citations
“…These findings, which are substantially different from what observed in Cs 2 AgBiBr 6 NCs (where akylammonium ions only have been detected), 14 point to a complex ligand shell in which ligands are homogeneously intermixed on the surface of perovskite NCs.…”
contrasting
confidence: 91%
“… 33 36 While our knowledge of the surface passivation of Pb-based perovskite NCs is reaching maturity, we know much less on the ligand shell of double perovskite NCs. 14 , 37 41 To date, only the ligand shell of Cs 2 AgBiBr 6 NCs has been examined by Zhang et al, who concluded that the only species passivating the surface are alkylammonium ions. 14 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This capping ligand layer thickness is slightly smaller than the 1.5–1.8 nm length of a buckled C 17 hydrocarbon chain . Ligand layers with similar thickness have also been reported for oleylamine and oleic acid‐capped double perovskite nanocrystals in superlattices . The GIWAXS pattern in Figure D is indexed to TlBr with CsCl crystal structure.…”
Section: Resultssupporting
confidence: 66%
“…When the reaction temperature exceeded 140 °C, additional TlBr nanocrystals also formed (see Supporting Information Figure S3). The need for short reaction times is similar to other metal halides, such as CsPbI 3 or Cs 2 AgBiBr 6 . Perhaps rapid quenching of nanocrystal growth reactions is more generally necessary for perovskite and related metal halide nanocrystals with tertiary or quaternary composition than binary compounds .…”
Section: Resultsmentioning
confidence: 99%